Comparison of lactate threshold, ventilatory threshold, and heart rate deflection point in female rowers - Vukovich, M. D.; Alton, M. (Medicine & Science in Sports & Exercise, 1996)
The associations between the heart rate deflection point (HRd) and lactate (LT), OBLA (4mM), and ventilatory thresholds were assessed using female collegiate rowers performing a rowing ergometer task. It was found that HRd occured in female rowers and coincided with VT and (OBLA). However, HRd did not coincide with LT and did not appear to be a strong predictor of LT or OBLA. Implication This is another example of the dubious value of heart rates for predicting other aspects of the exercise response. It appears to be of little value for female rowers and estimating lactate threshold.